(untitled) (Physical Culture and Sport: Scientific Perspective, 2023)
Statement of the problem in general and its connection with important scientific and practical tasks. The article is devoted to the study of the process of formation of professional and applied physical training (PAPT) of students of different educational and professional programs. The preparation of young people for the challenges and needs of society suggests that due attention should be paid to physical education programs for future professionals. The necessity of analytical assessment of the level of physical health of students and means for its maintenance and restoration is shown. It is noted that physical education classes are a necessary step towards the formation of professional and applied physical training of students of different specialties. The pedagogical conditions for the formation of professional and applied physical training of students of different specialties are substantiated (the first condition is to ensure the effectiveness of the content of the physical education program, the connection of forms, methods and means of physical training, the second condition is the analysis of the level of physical health of young people, planning and organization of the educational process, the third condition is the development and implementation of a classification of means and methods to ensure effective physical training of students of different specialties). It is shown that students have different attitudes to physical exercises: the first place is occupied by strength exercises (40%) (exercise machines, exercises with weights, jumping exercises), cardio exercises are in second place (28%), (walking, running, swimming, cycling, skiing, skating), breathing exercises (17%) (breathing exercises, cyclic breathing, square, abdominal breathing, cyclic sighing, square breathing) and stretching exercises (12%) (lunges, butterfly exercise, shoulder stretch, leg bend, arm stretch, side lunges with squat).